2017
DOI: 10.1002/2017ja024535
|View full text |Cite
|
Sign up to set email alerts
|

MMS Observation of Magnetic Reconnection in the Turbulent Magnetosheath

Abstract: In this paper we use the full armament of the MMS (Magnetospheric Multiscale) spacecraft to study magnetic reconnection in the turbulent magnetosheath downstream of a quasi‐parallel bow shock. Contrarily to the magnetopause and magnetotail cases, only a few observations of reconnection in the magnetosheath have been reported. The case study in this paper presents, for the first time, both fluid‐scale and kinetic‐scale signatures of an ongoing reconnection in the turbulent magnetosheath. The spacecraft are cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
79
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4
1

Relationship

4
5

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 85 publications
0
79
1
Order By: Relevance
“…Here J is the current density, E ′ is the electric field in the moving frame of electrons, and Q is the dimensionless agyrotropy calculated from the electron pressure tensor. These values might correspond to the outer EDR (Vörös et al, ). MMS3 also observed two electron outflows at 00:23:55.08 and at 00:23:56 UT with V e ⊥ L ∼ −75 km/s, when the spacecraft was inside the IDR (Figures a and e).…”
Section: Mr and Wave Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here J is the current density, E ′ is the electric field in the moving frame of electrons, and Q is the dimensionless agyrotropy calculated from the electron pressure tensor. These values might correspond to the outer EDR (Vörös et al, ). MMS3 also observed two electron outflows at 00:23:55.08 and at 00:23:56 UT with V e ⊥ L ∼ −75 km/s, when the spacecraft was inside the IDR (Figures a and e).…”
Section: Mr and Wave Observationsmentioning
confidence: 99%
“…Between 00:23:52.7 and 00:23:54.2 UT the low‐energy electron population, which has the largest contribution to Te , becomes parallel and antiparallel to the magnetic field (Figure i). Field‐aligned electrons are energized by parallel electric field at the boundary of the EDR at around 00:23:54 UT (see Vörös et al, ). The resonant energies for the whistler waves can be estimated from the resonance condition V ‖ res =( f − f ce ) λ ‖ , where λ=Vphwfalse/f is the parallel wavelength.…”
Section: Whistler Wavesmentioning
confidence: 99%
“…Based on Cluster data, Retinò et al () observed many current sheets in the magnetosheath (shock downstream region) and reported reconnection. Yordanova et al () and Vörös et al () demonstrated signatures of ion and electron diffusion regions in magnetosheath current sheets observed by MMS. Based on MMS data, Phan et al () showed electron‐scale current sheets exhibiting reconnection in the magnetosheath, where only electron but no ion jets were detected, indicating that ions cannot respond to the small‐scale structures, and only electrons are involved in reconnection.…”
Section: Introductionmentioning
confidence: 95%
“…Reconnection is also demonstrated in particle‐in‐cell simulations relevant to astrophysical (high M A ~ 40) quasi‐perpendicular shocks ( θ Bn > 45°), where current sheets are generated through the Weibel instability, and the magnetic islands generated by reconnection accelerate electrons to suprathermal energies (e.g., Matsumoto et al, ). Evidence of reconnection has been reported to occur in the magnetosheath downstream of the Earth's bow shock (Eriksson et al, ; Phan et al, ; Retinò et al, ; Vörös et al, ; Wilder et al, , ). Features of current sheet structures consistent with magnetic reconnection were identified in the transition region of a quasi‐parallel shock in a recent study (Gingell et al, ).…”
Section: Introductionmentioning
confidence: 99%